Effect of heating rate on the quality of Longjing tea during baking and aroma -improving process - ZHU Zuochun; TANG Yi; PAN Rong; HU Shuqin (浙江大学学报. 农业与生命科学版)
In the tea refining process, baking and aroma-improving technology is widely used in many kinds of dry tea to improve and stabilize the tea quality. Through baking process, not only the moisture of tea could be effectively reduced but also the harmful bacteria could be killed, which is good for preservation; furthermore, baking promotes the dehydration saccharification and isomerization of tea components which is good for tea quality by the way of reducing the bitterness, astringent taste and removing stale taste and miscellaneous taste of tea. So far, research on baking and aroma-improving technology was limited to baking temperature, baking time and so on. Considering that different heating rates in baking and aroma-improving process has different thermal effects on tea. It usually heats up faster on tea surface, but slower inside the tea due to the thermal conductivity factor, therefore, fast heating rate usually leads to uneven heating effect and to the decreases of tea quality. In this work, baking treatments with different heating rates were applied to Longjing tea, and the effects of heating rates on the tea quality were investigated.Middle and low grade Longjing teas were used as tested materials. Different baking treatments were carried out with final temperature of 110℃ and heating rates of 4, 6 and 8 ℃/min respectively. Treatment A4 was directly heated at 110℃ for 45 minutes, and the unheated Longjing tea as a control. Different baking time was implemented in accordance with different heating rates to ensure that all the tea with different treatments received the same total heat. The effects of heating rate on the tea quality were estimated by sensory evaluation, quality component determination and gas chromatography-mass spectrum (GC-MS) for aroma analysis.The results indicated that different heating rates in baking process had obvious impact on the tea quality. Values from chemical tests showed that the slow heating rate resulted in the higher contents of amino acids and chlorophyll and the lower contents of tea polyphenols, implying better quality compared with other treatments, which was consistent with the results of sensory evaluation. The heating rate also had significant effects on the aroma quality of tea. Slow heating rate resulted in the higher contents of β-myrcene, ocimene, trans-linaloloxide, linalool and nonanal, which were characteristic constituents of clean aroma and were good for the flavor quality of the tea, than the fast heating rates did. While the fast heating rate or direct baking led to high-fired taste and scorched flavor.It is concluded that compared with the fast heating rate, the slow heating rate in baking and aroma-improving process obviously improves the colour, flavor and taste quality of tea, indicating that it is hopeful to find a way for further improvements in baking technology.